Proceedings of the 2nd International Conference on ICT for Digital, Smart, and Sustainable Development, ICIDSSD 2020, 27-28 Feb 2021
DOI: 10.4108/eai.27-2-2020.2303137
|View full text |Cite
|
Sign up to set email alerts
|

IOT based Automation for Smart Sustainable Homes

Abstract: This paper proposes the design of Inter of Things (IoT) based home automation system using Raspberry pi. Unlike the conventional fixed switches for switching on and off-fans, bulbs and other electrical devices , it would provide users portable control and management all the devices connected together over wireless local area network. Moreover this paper lays emphasis on the security of the user's home by providing biometric door lock/unlock feature through fingerprint sensor of a smart phone. This paper also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Sohag et al [10] proposed waste management and it is found to be very efficient over the traditional waste management systems. Samad et al [11] proposed a model to implement IoT in smart homes to manage and control electrical devices from a remote location within a Wi-Fi network. The paper highlighted user-friendly, water conservation for simple and sustainable homes in turn contributes to goal 6 of SDGs.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Sohag et al [10] proposed waste management and it is found to be very efficient over the traditional waste management systems. Samad et al [11] proposed a model to implement IoT in smart homes to manage and control electrical devices from a remote location within a Wi-Fi network. The paper highlighted user-friendly, water conservation for simple and sustainable homes in turn contributes to goal 6 of SDGs.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The majority of researches which are conducted in the Sciences especially, the Computer Science discipline are of attempts made to build IoT models in the context of building smart homes. A negligible component of Sustainability, Green Smart Homes, Energy Conservation and Water Conservation is considered for instance, [11], [10], [13], [9].…”
Section: Research Gapsmentioning
confidence: 99%
“…In our rapidly evolving digital age, the Internet of Things (IoT) has emerged as a critical smart application for modern security living [3][4][5][6][7][8][9]. Integrating IoT devices, automation…”
Section: Introductionmentioning
confidence: 99%
“…IoT 2024, 5 detection, and notification systems with smart home technology offers a comprehensive security solution for everyday activities [8,10,11]. Cost optimization and facilitation are significant benefits provided by IoT-driven transformations for real-time remote-access systems [12] through cellular and Wi-Fi networks [4,6,13]. Integrating mobile access points within an IoT-driven home security system can significantly enhance the system's ability to manage energy resources and maintain robust communication with various sensors and devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation